HUBUNGAN METODE MENGAJAR DENGAN MINAT BELAJAR DI MTs AISYIYAH UJUNG BELAKANG OLO PADANG - Dinil Abrar Sulthani (POTENSIA: Jurnal Kependidikan Islam, 2017)
This research aims to describe about teaching methode of teachers, learning interest students, and to determine the relationship between teaching method of teachers and learning interest students in MTs Aisyiyah Ujung Belakang Olo Padang. The research used the quantitative descriptive. The technique used to collect data in this study is the observation, the documentation, and the questionnaires. The findings showed that in MTs Aisyiyah Ujung Belakang Olo Padang: 1) teaching method of teachers is not good in presentation in the class, 2) learning interest students is lower, and 3) this study also indicate that relationship between teaching method of teachers and learning interest students.